Neonatal outcome in deliveries complicated by meconium-stained amniotic fluid - Shah, Parul T.; Kothari, Kinjal A.; Patel, Rina V.; Panchal, Payal P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Meconium staining amniotic fluid is associated with lots of adverse outcome and has long been considered to be a bad predictor of fetal outcome. This prospective observational study was undertaken to find out immediate fetal outcome in meconium-stained liquor. Methods: The design of the study was prospective. This study was conducted from July 2021 to December 2021.The study included women with meconium-stained amniotic fluid in labor with gestational age >37 completed weeks. Results: Total 100 cases were enrolled. Majority of the patients (74%) were in the age group of 21-30 years with the mean age being 24.6±2.4 years. Fetal distress occurred in 30% of babies, more in association with thick meconium (15%). Caesarean deliveries were 70%. Apgar scores between 0-3 was seen in 17% babies and 1% at fifth minute, between 4-6 in 21% babies and between 7-10 in 62% babies at first minute of birth. Admission in neonatal ward was 32% with perinatal mortality of 6%. Conclusions: Meconium-stained amniotic fluid was associated with higher rate of caesarean delivery, increased need for neonatal resuscitation, increased rate of birth asphyxia with hypoxic ischemic encephalopathy, meconium aspiration syndrome, hospital admission and mortality. It is more commonly associated with pregnancy induced hypertension (PIH), post-datism, oligohydramnios and gestational diabetes mellitus.